Thirsty Energy : Understanding the Linkages between Energy and Water - Delgado, Anna (World Bank, Washington, DC, 2015)
Population growth and economic development, aggravated by climate change, will increase pressure on energy and water resources. Integrated planning can make the most of these two essential and scarce resources. Thirsty Energy, a World Bank initiative, helps countries address these issues and ensure sustainable development of both resources. This note focuses on the water needs of the power sector and particularly answers the following questions: Why is this issue important? Do power plants need all that much water? What about other types of plants? What are the challenges? and, What are our options?